Effects of Mindfulness with Gayatri Mantra on Decreasing Anxiety in the Elderly - Sang Ayu Ketut Candrawati; Meidiana Dwidiyanti; Rita Hadi Widyastuti (Holistic Nursing and Health Science, 2018)
Background: Anxiety is one of the psychological problems which can develop in the elderly. If left untreated, it can decrease the productivity and quality of life. Mindfulness with Gayatri mantra is such a complementary therapy which is effective to reduce anxiety in the elderly.  Objective: The purpose of this study was to determine the effects of mindfulness with Gayatri mantra on decreasing anxiety in the elderly Hindus in Bali, Indonesia. Methods: This study employed a one group pre and posttest quasi-experimental design and involved 34 elderly people recruited using a purposive sampling technique. Anxiety was measured using the Geriatric Anxiety Scale (GAS). A t-test statistical analysis was used to analyze the data.   Results: Results showed that there were significant effects of mindfulness with Gayatri mantra on decreasing the anxiety in the elderly Hindus in Bali with a p-value of 0.000 (α-value = 0.05). Conclusion: Mindfulness with Gayatri mantra could decrease anxiety in the elderly Hindus. This therapy can be used as an alternative to prevent the recurrence of anxiety in the elderly.